Suppressed Recombination of Sex Chromosomes Is Not Caused by Chromosomal Reciprocal Translocation in Spiny Frog (Quasipaa boulengeri) - Yuan, Xiuyun; Xia, Yun; Zeng, Xiaomao (Frontiers in Genetics, 2018)
Chromosome rearrangements (CRs) are thought to be related to sex chromosome evolution, but it is controversial whether CRs are the initial causative mechanism of suppressed recombination for sex differentiation. The early stages of sex chromosome evolution in amphibians may represent intermediate states of differentiation, and if so they potentially shed light on the ultimate cause of suppressed recombination and the role of CRs play in sex chromosome differentiation. Here, we showed that sex determination differs among 16 populations of spiny frog, Quasipaa boulengeri, in which individuals have normal and rearranged chromosomes caused by reciprocal translocation. In eastern areas, without translocation, genetic differentiation between sexes was relatively low, suggesting unrestricted recombination. Comparatively, in western populations that have both normal and translocated chromosomes, a male-heterogametic system and lack of X-Y recombination were identified by male-specific alleles and heterozygote excess. However, such genetic differentiation between sexes in western populations was not directly related to karyotypes, as it was found in individuals both with normal and translocated karyotypes. In western Sichuan Basin, male-specific and translocation-specific allelic frequency distributions suggested that recombination of sex-differentiation was ceased in all populations, but recombination suppression caused by translocation did not exist in some populations. Combined with phylogenetic inference, it indicated that the establishment of the sex-linkage had taken place independently of reciprocal translocation, and translocation was not the ultimate cause of sex chromosome differentiation. Furthermore, comparison of the genetic diversity of the alleles on Y chromosomes, X chromosomes and autosomes in western populations showed a reduction of effective population size on sex chromosomes, which may be caused by reciprocal translocation. It indicates that, although it is not the ultimate cause of recombination suppression, reciprocal translocation may enhance sex chromosome differentiation.